The Influence of Workload on the Performance of Officers in Class II A Muara Beliti Narcotics Prison - Farid, Anwar; Jarodi, Odi (prodima@fe.uika-bogor.ac.id, 2023)
This study aims to determine the cause and magnitude of the effect of workload on the performance of the Class II A Narcotics Prison officers in Muara Beliti. This study uses quantitative research methods and uses an experimental design to determine the cause and magnitude of the influence of the independent variable (work-load) on the dependent variable (performance). Simple linear regression analysis was used in this study as a data analysis tool to determine the magnitude of the effect of workload on the performance of Class II A Narcotics Prison officers in Muara Beliti. There are 2 sources of data used in this study, namely primary data sources by distributing questionnaires via Google form and secondary data sources, namely books, the internet, and journals related to research. Probability sampling is used in this study as a sampling technique with a simple random sampling type because all members of the population have the right to be the research sample, then the sampling method using the Slovin formula is used to narrow the population. This research shows that there is a positive influence and significance of the independent variable (workload) on the dependent variable (performance) with the magnitude of the influence of 63.4%.